The Effect of Product Quality and Promotion on Mcdonald's Brand Image Through Customer Loyalty in The Middle of The Pro-Zionist Boikot Issue - Fahriah, Atikah Firyal; Dzakwan, Muhammad Roem; Ramadhani, Muh Awal; Nuraisyah; Hasnidar (Journal of Economics and Management Technologies, 2025)
The Objectives – This study aims to analyze the effect of product quality and promotional strategies on McDonald's brand image through customer loyalty, especially in the context of the growing pro-Zionist boycott issue in Indonesia. The Methods – An explanatory quantitative approach was used with data collection through a closed questionnaire to 250 respondents who are McDonald's customers. The results of the analysis using Structural Equation Modeling (SEM) show that product quality and promotion have a significant influence on brand image, both directly and indirectly through customer loyalty as a mediating variable. The Results – This finding shows that despite political pressure in the form of boycotts, McDonald's is able to maintain a strong brand image through a combination of consistent product quality, effective promotional strategies, and high customer loyalty. The Research Implications – This research provides theoretical and practical contributions to the development of marketing strategies in situations of reputation crisis and political pressure.